Substitution or Symbolic Effects? A Reexamination of Corporate Governance and Firm Performance - GENG, Xuesong (Institutional Knowledge at Singapore Management University, 2006)
In this paper, we use a sample of large Canadian corporations to test the substitution hypothesis and the symbolic hypothesis. We find that the positive effect of board independence on firm performance declines as managerial ownership increases. This effect becomes non-positive when highly concentrated managerial ownership makes independent board more symbolic than effective.